2003
DOI: 10.1021/bi0347407
|View full text |Cite
|
Sign up to set email alerts
|

Water−Hydroxide Exchange Reactions at the Catalytic Site of Heme−Copper Oxidases

Abstract: Membrane-bound heme-copper oxidases catalyze the reduction of O(2) to water. Part of the free energy associated with this process is used to pump protons across the membrane. The O(2) reduction reaction results in formation of high-pK(a) protonatable groups at the catalytic site. The free energy associated with protonation of these groups is used for proton pumping. One of these protonatable groups is OH(-), coordinated to the heme and Cu(B) at the catalytic site. Here we present results from EPR experiments o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 30 publications
4
44
0
Order By: Relevance
“…After 2 electrons enter the BNC to form the R (OORR) intermediate, the aquo-cofactor's pK a s are greater than 7 so both remain protonated as calculated previously (33). This result agrees with experiments that show little proton release at pH 7 when CO is photolyzed off the mixed valence complex, initiating backelectron transfer moving from the OORR to OROR state (34). The pK a obtained from the fractional site ionization in Monte Carlo sampling as a function of pH for aquo-heme a 3 is 8.6, in good agreement with the measured pK a of 9 for proton release.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…After 2 electrons enter the BNC to form the R (OORR) intermediate, the aquo-cofactor's pK a s are greater than 7 so both remain protonated as calculated previously (33). This result agrees with experiments that show little proton release at pH 7 when CO is photolyzed off the mixed valence complex, initiating backelectron transfer moving from the OORR to OROR state (34). The pK a obtained from the fractional site ionization in Monte Carlo sampling as a function of pH for aquo-heme a 3 is 8.6, in good agreement with the measured pK a of 9 for proton release.…”
Section: Resultssupporting
confidence: 87%
“…Thus, with Cu B reduced, the reduction of heme a, not heme a 3 , is calculated to be coupled to the proton binding into the BNC (Table 1). When the second electron is transferred from heme a into the BNC, there are only small changes in total protonation, in agreement with the experiments photolyzing the CO-heme a 3 bond in the mixed valence OORR state (34). Reduction of all four cofactors moving from the OOOO to RRRR state is coupled to the uptake of 2.5 protons ( Table 1).…”
Section: Resultssupporting
confidence: 85%
“…Results from earlier studies have shown that the PCET rate is independent of the composition of the buffer or its concentration (17,21), which indicates that buffer molecules do not act as proton donors or acceptors for the protons released through the K pathway. As the observed PCET rate represents the sum of the release and uptake rates, it is not straightforward to calculate a second-order proton-uptake rate constant.…”
Section: Discussionmentioning
confidence: 97%
“…The proton donor is a water molecule at the catalytic site, which interacts electrostatically with heme a 3 . Upon proton release, the formed hydroxide binds to the oxidized heme a 3 (21). Even though this proton release occurs in the opposite direction to that during turnover, the kinetics of the proton-coupled electron transfer (PCET) reflects both the proton uptake and release rates (the sum of these rates) through the K pathway (15,17).…”
mentioning
confidence: 99%
“…Calculations are also carried out on cytochrome c oxidase. Here the pK a is compared with the pH dependence of the proton release on oxidation of heme a 3 (53). Several of these proteins have positively charged groups in the active site.…”
mentioning
confidence: 99%